Uji Fitokimia dan Toksisitas Ekstrak Umbi Hydnophytum sp. terhadap Artemia salina Leach - Nur Wakidatul Khasanah; Bhakti Karyadi; Agus Sundaryono (PendIPA Journal of Science Education, 2020)
The goal of this research was to determine the content of secondary metabolites and the most active fraction of Simbagh Utak (Hydnophytum sp.) Tuber extracts. The content of secondary metabolites is determined by using phytochemical tests, and toxicity tests are carried out by the Brine Shrimp Lethality Test (BSLT) method. Hydnophytum bulbs from Jukung Village, Lubuklinggau City, South Sumatra were macerated using 96% ethanol and then evaporated until thick extracts were obtained. This thick extract was then tested for secondary metabolite content, fractionated using n-hexane, and ethyl acetate. The results of the fractionation were then carried out a toxicity test using the BSLT method. Secondary metabolite test results showed ethanol extract containing flavonoids, alkaloids, tannins, saponins, terpenoids, and phenolics. The result of fractionation was obtained by the tuber extract of Hydnophytum n-hexane fraction, ethyl acetate fraction, and ethanol fraction. Toxicity test results obtained LC50 values of n-hexane fraction of 52.3 ppm, LC50 of ethyl acetate fraction of 45.9 ppm, and LC50 of ethanol fraction of 99 ppm. All Hydnophytum tuber extract fractions were categorized as toxic and have potential as anti-bacterial or anti-oxidant. The fraction that has the lowest LC50 price is the most toxic fraction. The most toxic fraction is the most active fraction. The ethyl acetate fraction was the most active fraction because it has the lowest LC50.